PENGEMBANGAN TINDAK BAHASA TERAPI DALAM INTERVENSI ANAK AUTIS SPEKTRUM PERILAKU - Prasetyoningsih, Luluk Sri A. (LITERA, 2016)
This study aims to develop a prototype of therapeutic language acts for the intervention in children with behavioral spectrum autism. This was a research and development study employing the R2D2 (Recursive, Reflective, Design, and Development) model. It consisted of product design, product validation, tryout, product revision, and mass production. The prototype of therapeutic language acts was collaboratively developed by involving the developer, expert team (a language expert and a clinical expert), and practitioner (a therapist). The data were collected through observations, field notes, and questionnaires. The results show that the developed prototype of therapeutic language acts satisfies the criteria for accuracy, utility, and appropriateness. The conclusion is that the prototype of therapeutic language acts for the intervention in children with behavioral spectrum autism satisfies the criteria for acceptability and can be used as a reference to deal with children with behavioral disorder autism.